Rainfastness of glyphosate as affected by surfactants on Paspalum conjugatum P.J Bergius - Musa, Izat Ezatte (2016)
Weeds are major pest on crop plantation in Malaysia, especially in rubber and oil palm plantations. In Malaysia, Paspalum conjugatum is most commonly found in plantations. Paspalum conjugatum, a perennial or annual weed species from family of Poaceae is distinct among many invasive plant species because of it strongly stoloniferous characteristic and easy to spread out. In order to overcome the problem of P. conjugatum, glyphosate is used to control the growth of Paspalum conjugatum. Glyphosate is one of the broad-spectrum systemic herbicide that can be used to control this weed. The efficacy of glyphosate can be improved by adding surfactant in the spray solution. Nevertheless, rainfastness is one of the important factors affecting the efficacy of foliar applied herbicides. Rainfall that occurs after application will have significant effect on the residual activity and efficacy of herbicides. The research was conducted to determine the influence of surfactants on rainfastness of glyphosate on Paspalum conjugatum. The experiment was conducted in Field 2, UPM Serdang. Treatments used were Glyphosate + 0.025% Silwet408, Glyphosate + 0.14% Bond Adjuvant, Glyphosate + 0.05% Miracle S240, Glyphosate + 0.1% KaO A-134, Glyphosate alone and control. The spraying was conducted on eight week after transplanting followed by exposure to rainfall using rainfall stimulator for 1 and 3 hours after spraying. There were 6 treatments with 5 replications for each treatment. Results showed significant different between before and after rain on spray deposition, chlorophyll content and necrosis. No significant different was observed after exposure to rain 1 and 3 h after application. Glyphosate + 0.14% Bond Adjuvant produced a better performance on spray deposition, chlorophyll content and necrosis compared with other surfactants.